ANALISIS POLA BELAJAR NUMERIK PADA ANAK TUNAGRAHITA DI SLB NEGERI CENDONO KUDUS - Martha Setiawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Writing this article aims to find out the pattern of numerical learning in mentally retarded children at the Cendono Kudus State SLB, this is oriented towards "objective analysis and observation". Therefore the researcher conducted this research to discuss more deeply how students' learning patterns relate to numerical learning, whether students can follow it well or not.